Inventarisasi Parasitoid Hama Tanaman Padi Sawah di Kabupaten Minahasa Utara - Ariyane O.S. Siwu; Jantje Pelealu; Christina L. Salaki; Noni N. Wanta (Universitas Sam Ratulangi, 2013)
ABSTRACTInsect parasitoids are small or as large as the host to parasite and off the host. The research was conducted in lowland rice planting area in North Minahasa regency. Research purposes to determine the type and parasitoid populations on rice crop pests in sub Kauditan, Talawaan, and Dimembe. The research was done by sweeping using insect net swing of 20 times on the location of paddy rice crops, sampling is done three times at intervals of two weeks representing all phases of rice growth was identified in the laboratory and then analyzed descriptively. The results showed that the insect parasitoid found was of the Order Hymenoptera and Diptera and in different types and each sub-population, namely, District Kauditan there are 19 types, 19 types Talawaan, and Dimembe13 types. Parasitoids Telenomus spp. average of 6.5 tail in Kauditan, Dimembe 4.5 tail, while the tail Talawaan 3.6 Apanteles sp. average of 6.5 in sub Dimembe tail, Talawaan 6 tails, and tails Kauditan 3.8.Keywords :Parasitoids, Hymenoptera, Diptera, Rice plants